Effects of gum chewing on glycaemic control in women with gestational diabetes mellitus: A randomized controlled trial. Impact of chewing on hyperglycaemia in women with GDM. (April 2020) - Yerlikaya-Schatten, Gülen; Trimmal, Lisa; Rosicky, Ingo; Husslein, Peter; Schatten, Christian; Eppel, Daniel; Eppel, Wolfgang; Tura, Andrea; Göbl, Christian S.
Abstract: Background: The amount of chewing might be relevant in reducing hyperglycaemia in diabetic patients. The study assessed the impact of enhanced chewing on glycaemic control in women with gestational diabetes mellitus (GDM). Methods: As an open-label, mono-centre randomized controlled trial, 59 women with recent diagnosis of GDM were included. They received either routine care or additional chewing gum intervention. SMBG was performed for five days. Results: No significant impact on mean values of postprandial glucose levels were observed. The estimated mean differences (intervention vs. control group) were: 4.9 mg/dl, 98.4 %CI -7.2–17.1 (breakfast); -4.5 mg/dl, 98.4 %CI -15.1–6.0 (lunch); -3.8 mg/dl, 98.4 %CI -15.9 to 8.4 (dinner). OGTT levels at 60 and 120 min. were associated with glucose levels after breakfast. Conclusion: In conclusion, no significant differences in blood glucose levels were observed between the groups and therefore major effects of chewing on hyperglycaemia in women with GDM could be excluded. Trial registration: ClinicalTrials.gov; NCT03961542, Date of registration: 20.01.2019. Retrospectively registered